Unlocking cellular plasticity: enhancing human iPSC reprogramming through bromodomain inhibition and extracellular matrix gene expression regulation - Yang, Jun; Kinyamu, H Karimi; Ward, James M; Scappini, Erica; Muse, Ginger; Archer, Trevor K (Stem cells (Dayton, Ohio), 2024)
The transformation from a fibroblast mesenchymal cell state to an epithelial-like state is critical for induced pluripotent stem cell (iPSC) reprogramming. In this report, we describe studies with PFI-3, a small-molecule inhibitor that specifically targets the bromodomains of SMARCA2/4 and PBRM1 subunits of SWI/SNF complex, as an enhancer of iPSC reprogramming efficiency. Our findings reveal that PFI-3 induces cellular plasticity in multiple human dermal fibroblasts, leading to a mesenchymal-epithelial transition during iPSC formation. This transition is characterized by the upregulation of E-cadherin expression, a key protein involved in epithelial cell adhesion. Additionally, we identified COL11A1 as a reprogramming barrier and demonstrated COL11A1 knockdown increased reprogramming efficiency. Notably, we found that PFI-3 significantly reduced the expression of numerous extracellular matrix (ECM) genes, particularly those involved in collagen assembly. Our research provides key insights into the early stages of iPSC reprogramming, highlighting the crucial role of ECM changes and cellular plasticity in this process.